2021
DOI: 10.3390/nano11082120
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Efficacy of Metal and Metal Oxide Nanoparticles against the Porcine Reproductive and Respiratory Syndrome Virus

Abstract: Porcine reproductive and respiratory syndrome viruses (PRRSV) are responsible for one of the most economically important diseases affecting the global pig industry. On-farm high-efficiency particulate air (HEPA) filtration systems can effectively reduce airborne transmission of PRRSV and the incidence of PRRS, but they are costly, and their adoption is limited. Therefore, there is a need for low-cost alternatives, such as antimicrobial filters impregnated with antiviral nanoparticles (AVNP). During the past 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
(44 reference statements)
0
7
0
Order By: Relevance
“…In addition to the antibacterial effect, Cu-based NPs also have potent antifungal activity; for example, Ghasemian et al studied the antifungal activity of Cu-based NPs in killing pathogenic fungi, such as Alternaria alternata , Aspergillus flavus , Fusarium solani , and Penicillium chrysogenum , and found that 8 nm has better antifungal activity with a minimum inhibitory concentration of 40–80 mg/L. Besides, Cu-based NPs also have a high ability to resist viral infection, such as Hepatitis C Virus, Porcine reproductive and respiratory syndrome viruses (PRRSV), and SARS-CoV-2 . Therefore, the strong microbicidal properties make Cu-based NPs widely used in the biomedicine industry as well as agricultural industry such as plants and livestock fields. , …”
Section: Application and Toxicity Of Copper-based Nanoparticlesmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the antibacterial effect, Cu-based NPs also have potent antifungal activity; for example, Ghasemian et al studied the antifungal activity of Cu-based NPs in killing pathogenic fungi, such as Alternaria alternata , Aspergillus flavus , Fusarium solani , and Penicillium chrysogenum , and found that 8 nm has better antifungal activity with a minimum inhibitory concentration of 40–80 mg/L. Besides, Cu-based NPs also have a high ability to resist viral infection, such as Hepatitis C Virus, Porcine reproductive and respiratory syndrome viruses (PRRSV), and SARS-CoV-2 . Therefore, the strong microbicidal properties make Cu-based NPs widely used in the biomedicine industry as well as agricultural industry such as plants and livestock fields. , …”
Section: Application and Toxicity Of Copper-based Nanoparticlesmentioning
confidence: 99%
“…Besides, Cu-based NPs also have a high ability to resist viral infection, such as Hepatitis C Virus, Porcine reproductive and respiratory syndrome viruses (PRRSV), and SARS-CoV-2 . Therefore, the strong microbicidal properties make Cu-based NPs widely used in the biomedicine industry as well as agricultural industry such as plants and livestock fields. , …”
Section: Application and Toxicity Of Copper-based Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, CuO nanoparticles have been modi ed with BA as a model system and molecular dynamics simulation has also been performed for analyzing diffusivity, level of agglomeration, aggregation dependent on viscosity and interaction kinetics. 25 . Therefore, by conducting simulations on CuO dispersion in aqueous medium with surfactant (that holds properties of inhibition) can help in understanding the inhibiting science of these modi ed particles and how it degrades the production of viruses.…”
Section: Introductionmentioning
confidence: 99%
“…Today, in the current Covid-19 pandemic, the Cu/CuONPs have proved effective in killing SARS-CoV1/2 and other airborne viruses, as investigated by Ren and Lin in their latest research outcomes conducted in 2021 25 . Therefore, by conducting simulations on CuO dispersion in aqueous medium with a surfactant (that holds properties of inhibition) can help in understanding the inhibiting science of these modified particles and how it degrades the production of viruses.…”
Section: Introductionmentioning
confidence: 99%